Arrangements for Reclamation Obligations in Mineral and Coal Mining Businesses - Wibisono, Yohanes Kunto; Nurjaya, I Nyoman; Suhartono, Slamet; Mangesti, Yovita Arie (Technium Social Sciences Journal, 2022)
The purpose of this research is to determine how the reclamation obligations regulation in the mineral and coal mining business in Indonesia. This study uses normative legal research methods, namely research that departs from the inconsistency between common conditions (das Sollen) and reality (das Sein). The results of this study are that the government has determined mining activities starting from implementing mining business activities to reclamation and post-mining activities. Regulations regarding legal sanctions provide hope that can become a legal objective in terms of guaranteeing legal certainty, justice, and sustainable benefits for society so that the objectives of the law can be fulfilled. Construction of the substance of reclamation arrangements for mineral and coal mining businesses still needs to answer the objectives of positive law in Indonesia.